The traitor - Burrowes, Grace (Burrowes, Grace. Captive hearts, 2014)
"Abandoned in France since boyhood, despite being heir to an English barony, Sebastian St. Clair makes impossible choices to survive a tour of duty in the French Army. He returns to England hoping for the peaceful life of a country gentleman, though old enemies insist on challenging him on the field of honor, one after another. Millicent Danforth desperately needs her position as companion to the Traitor Baron's aunt, but grieves to learn that Sebastian must continually fight a war long over. As Sebastian and Milly explore their growing passion, they uncover a plot that will cost Sebastian his life and honor, unless he does battle once more."--back cover.